Forage Quality of Bajra × Napier Hybrid cv. Phule Jaywant as Affected by Growing Environments and Nitrogen Levels - Damame, S. V.; Gore, S. B.; Sinare, B. T.; Gavit, M. G.; Pardeshi, H. P. (Indian Journal of Animal Nutrition, 2017)
An experiment was conducted at research farm of AICRP on Forage Crops and Utilization, MPKV, Rahuri, Maharashtra to assess the effect of growing environments and nitrogen levels on yield and quality ofbajra (Pearl millet) × Napier hybrid fodder crop (B x N hybrid cv. Phule Jaywant). The experiment was laid out in split plot design using growing environments as main plot and different levels of nitrogen as sub plots. Plantation was carried out at 90 cm × 60 cm using rooted slips of B × N hybrid cv. Phule Jaywant on ridges andfurrows. The treatment plots for shaded conditions were planted below the mango trees and unshaded was in open sunlight nearby the orchard. Soil of experimental site was neutral in reaction, low in organic carbon and available nitrogen, medium in available phosphorus and very high in available potassium content. The nitrogen levels were 50, 75, 100 and 125% of recommended dose of nitrogen (RDN). The forage quality of the different cuts was analyzed at an interval of 40 days. The DM, CP and digestible DM yield increased (P